Beyond Stoicism: an Epicureanism Glance at Shakespeare’s Antony and Cleopatra - Sulaiman Alhmdni, Thulfiqar Abdulameer; Abbas Muraab , Hayder Mohammed (International Journal of Psychosocial Rehabilitation, 2019)
This work aims to analyze the principles of ancient philosophies of Stoicism and Epicureanismandthe modernist thinkers attitudethat showed how ideology reigns supreme.Shakespeare’sAntony and Cleopatra, when read for the first time, seems to be a play about thirst for power in which there is a victor, Octavian, and the vanquished, Antony and Cleopatra. But there is more to this play than meets the eye throughout analyzing and contrasting outlooks of two countries Rome and Alexandria, it became ascertained that this play is more about the battle of ideas and social beliefs than other issues. Also, George R.R. Martin’s A Game of Thrones, seems in contrast to these Stoicism and Epicureanism attitudes, by drawing upon Pierre Bourdieu’s theory of practice and Habituslikewise for Lacanian perspective, which refers to the lifestyle, values, dispositions and expectations of particular social groups that are achieved by the activities and experiences of everyday life. It seems that every value for which they strive for is contextualized and they live in a prison of ideas, so reality is under question. In addition, this study intends to show how our material context of existence produce our numerous experiences of possibilities and impossibilities, probable and improbable consequences, and in turn mold our unconscious sense of the possible, probable and essentially desirable for us.